2014
DOI: 10.2903/sp.efsa.2014.en-636
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli and Enterobacteriaceae counts on poultry carcasses along the slaughter processing line, factors influencing the counts and relationship between visual faecal contamination of carcasses and counts: a review

Abstract: A literature review was conducted covering the period 2000-2012 to gather information concerning the presence and counts of E. coli and Enterobacteriaceae on carcasses during different stages of the slaughter processing line (review question 1); risk factors that could explain the variability of the counts of the indicator organisms (review question 2) and the relationship between the counts of indicator organisms and visual faecal contamination on carcasses (review question 3). In total, 72 papers, providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…This was in agreement with other studies that reported a decrease in E. coli and Enterobacteriaceae after washing, regardless of whether chlorine was added to the water (Berrang & Bailey, 2009;Kemp, Aldrich, Guerra, & Schneider, 2001;Northcutt, Berrang, Smith, & Jones, 2003;Oyarzabal, Hawk, Bilgili, Warf, & Kemp, 2004;Stopforth et al, 2007) or not (Goksoy, Kirkan, & Kok, 2004;González-Miret, Escudero-Gilete, & Heredia, 2006;Svobodová, Bořilová, Hulánková, & Steinhauserová, 2012). A systematic literature review commissioned by the EFSA showed that fecal contaminants (Enterobacteriaceae, E. coli) changed in the range of -0.05 to +0.83 CFU per ml rinse water or cm 2 after the evisceration step (Barco, Belluco, Roccato, & Ricci, 2014). Reduced microbial counts on the carcass after washing may either be due to a real reduction in microbial contamination, or caused by a more even redistribution of bacteria on a carcass, resulting apparently lower counts per area, while the total amount of bacteria on the carcass remains largely unchanged.…”
Section: ! Discussionsupporting
confidence: 91%
“…This was in agreement with other studies that reported a decrease in E. coli and Enterobacteriaceae after washing, regardless of whether chlorine was added to the water (Berrang & Bailey, 2009;Kemp, Aldrich, Guerra, & Schneider, 2001;Northcutt, Berrang, Smith, & Jones, 2003;Oyarzabal, Hawk, Bilgili, Warf, & Kemp, 2004;Stopforth et al, 2007) or not (Goksoy, Kirkan, & Kok, 2004;González-Miret, Escudero-Gilete, & Heredia, 2006;Svobodová, Bořilová, Hulánková, & Steinhauserová, 2012). A systematic literature review commissioned by the EFSA showed that fecal contaminants (Enterobacteriaceae, E. coli) changed in the range of -0.05 to +0.83 CFU per ml rinse water or cm 2 after the evisceration step (Barco, Belluco, Roccato, & Ricci, 2014). Reduced microbial counts on the carcass after washing may either be due to a real reduction in microbial contamination, or caused by a more even redistribution of bacteria on a carcass, resulting apparently lower counts per area, while the total amount of bacteria on the carcass remains largely unchanged.…”
Section: ! Discussionsupporting
confidence: 91%
“…The present document is the report on the experimental study. The report of the extensive literature review is published as two separate external scientific reports (Barco et al, 2014a;Barco et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant information to be included in the questionnaires was selected according to information gathered through the extensive literature review (Barco et al, 2014b) and incorporating the suggestions of veterinarians responsible for the selected slaughterhouses that were contacted and involved at the very beginning of the study. The veterinarians were requested to complete the slaughterhouse questionnaire at the first visit, while the batch questionnaire was filled in during each visit.…”
Section: Collection Of Relevant Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For Enterobacteriaceae the data obtained were quite controversial, and in some cases limited increases of the counts at the end of the air chilling process were reported (Barco et al, 2014). Salmonella was not detected in either of the samples.…”
Section: Resultsmentioning
confidence: 92%